2016
DOI: 10.14740/jocmr2643w
|View full text |Cite|
|
Sign up to set email alerts
|

Summary of Glaucoma Diagnostic Testing Accuracy: An Evidence-Based Meta-Analysis

Abstract: BackgroundNew glaucoma diagnostic technologies are penetrating clinical care and are changing rapidly. Having a systematic review of these technologies will help clinicians and decision makers and help identify gaps that need to be addressed. This systematic review studied five glaucoma technologies compared to the gold standard of white on white perimetry for glaucoma detection.MethodsOVID® interface: MEDLINE® (In-Process & Other Non-Indexed Citations), EMBASE®, BIOSIS Previews®, CINAHL®, PubMed, and the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…The majority of previous reviews have limited inclusion criteria to those patients who have exclusively undergone standard automated perimetry. Our approach enabled the inclusion of 150 OCT studies, markedly larger than previous meta-analyses; a Cochrane review by Michelessi et al[ 181 ] identified 63 OCT studies, Fallon et al[ 185 ] identified 47 studies, Ahmed et al[ 182 ] identified 84 studies, and Oddone et al[ 183 ] identified 34 studies. The larger number of studies included enabled a more robust meta-analysis and the analyses of several patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous reviews have limited inclusion criteria to those patients who have exclusively undergone standard automated perimetry. Our approach enabled the inclusion of 150 OCT studies, markedly larger than previous meta-analyses; a Cochrane review by Michelessi et al[ 181 ] identified 63 OCT studies, Fallon et al[ 185 ] identified 47 studies, Ahmed et al[ 182 ] identified 84 studies, and Oddone et al[ 183 ] identified 34 studies. The larger number of studies included enabled a more robust meta-analysis and the analyses of several patient subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucomatous progression can be assessed by structural testing, such as measuring the peripapillary RNFL thickness with spectral domain optical coherence tomography (SD-OCT)57 and/or functional testing with perimetry (VF testing). However, the correlation between these two types of measurements generally is poor.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-glaucoma surgery can be classified into two types: Procedures that facilitate the outflow of the aqueous humor, including aqueous humor shunts, and trabecular, goniotomy and iridotomy surgeries; and procedures that reduce aqueous humor secretion by destroying cells of the ciliary body, such as cyclocryotherapy and cyclophotocoagulation (11). However, the former group of procedures is flawed, due to scarring problems and their limited long-term effects, while the latter group lacks precise control and can only be utilized for patients with absolute glaucoma who have already lost their vision (12)(13)(14)(15). Therefore, there is an urgent need to develop more safe and effective therapeutic approaches for glaucoma.…”
Section: Introductionmentioning
confidence: 99%